Differences of brain electrical activity between moderate and severe obstructive sleep apneic patients: a LORETA study. (18th May 2016) - Toth, Marton; Kondakor, Istvan; Faludi, Bela
Summary: The effects of initiation of continuous positive airway pressure (CPAP) therapy on electroencephalographic (EEG) background activity were investigated in patients exhibiting both moderate ( n = 13) and severe ( n = 12) obstructive sleep apnea syndromes in the testing of the potential differences of alterations of brain electrical activity caused by chronic hypoxia between these two groups. A normal control group ( n = 14) was also examined. Two EEG examinations were achieved in each group: before and after first‐time CPAP therapy. Low‐resolution electromagnetic tomography (LORETA) was implemented towards localizing the generators of EEG activity in separate frequency bands. Prior to CPAP treatment, as a common direction of change, analysis with LORETA demonstrated increased activity in comparison with the patient and control groups. In the moderate group, significant changes were detected in the alpha2 band in the posterior cingulate cortex as well as in the beta1 band in the right posterior parietal cortex and the left supramarginal gyrus. In the severe group, significant changes were found in theta and alpha1 bands in the posterior cingulate cortex. Following CPAP treatment, these significant differences vanished in the severe group. In the moderate group, significantly decreased activity was seen in the beta3 band in the right fusiform gyrus. These findings potentially suggest a normalizing effect of CPAP therapy on EEG background activity in both groups of obstructive sleep apnea syndrome patients. Compensatory alterations of brain electrical activity in regions associated with influencing successful memory retrieval, emotional perception, default mode network, anorexia and fear network caused by chronic intermittent hypoxia could possibly be reversed with the use of CPAP therapy.